Mineralogia de solos representativos da fazenda experimental “Rafael Fernandes” município de Mossoró, RN - Silva, Ana Carla Rodrigues da (Universidade Federal Rural do Semi-Árido, 2017)
Soil is a key resource for life on Earth, however, it is necessary that we sustain its preservation and maintenance in order to find a sensible use. The mineralogical composition is an aspect that influences large part of physicochemical phenomena that occur in the pedosphere, which helps in the understanding of the pedogenesis, being an important characterization but less frequently discussed for soils in the semiarid region of State of Rio Grande do Norte. Thereby, this study’s goal was the comprehend the genesis and major formation processes of representative soils from Fazenda Experimental Rafael Fernandes farm, countryside area of Mossoró-RN, through mineralogical composition, mainly from the clay fraction, focusing the iron oxide genesis. Three representative soil profiles were selected: Typic Rhodustults (P1), Rhodic Haplustox (P2) and Typic Plinthustalfs (P3). Chemical analysis were performed to obtain the content of crystalline iron (Fed) and amorphous iron (Feo), and mineralogical analysis to obtain the mineral phases by x-ray diffractometry of natural and iron-free clay. Being observed soils with distinct pedogenetic processes. In the three profiles, and in all horizons, there are well-defined peaks of kaolinite (Ct), showing that this mineral is at a more advanced level of crystallinity. Mineralogy of clay fraction from the representative soils are similar, with the only distinction in the Plinthustalf area. The representative soils show high content of crystalline iron and low Feo/Fed ratio, indicating higher weathering progress in P1 and P2 mainly, with the P3 being the class that had higher ratio, due to desilication process which generates a higher degree of crystallinity of these minerals. The results allowed us to conclude that the representative soil from Fazenda Experimental Rafael Fernandes farm showed pedogenesis extremely influenced by the formation factors: climate, parent material and topography.
Monografia
Keywords: Processos pedogenéticos; Óxidos de ferro; Grupo barreiras; Pedogenetic process; Iron oxide; Grupo barreiras; CIENCIAS AGRARIAS::AGRONOMIA